A case study of the employees of the sports complex Proximity «Al-Mujahid BOUTABA BELKACEM, Municipality of AL-SAWARKH", state of EL-TAREF - ben zaraa, yazid; djabri, dallal (Journal of Social Sciences and Humanities, 2024)
This research aims to consider the relationship between the type of leadership style used and the level of organizational effectiveness among the workers in the Algerian institution according to the approach of the multiplicity of beneficiaries, and to determine the most appropriate leadership style to achieve this effectiveness, by studying the relationship between the use of a specific leadership style on the organizational effectiveness of the employees and the degree of its decline or its height in the foundation, Using the quantitative approach, the study relied on the use of statistical analysis of the research form that was distributed to the workers and tires of the Sports Complex Proximity to answer the central question: What is the nature of the relationship between the leadership style followed and the organizational effectiveness of the employees of the Sports Complex Proximity in AL-SAWARKH? To answer the basic hypothesis of the study: There is a significant relationship between the type of leadership style followed and the organizational effectiveness of the workers of the sports complex Proximity in Al-SAWARKH. In this study, the comprehensive survey method was applied to the small size of the study population, consisting of 15 individuals representing the workers and executives of the establishment. Through a research form divided into four axes, the validity and stability of its elements that study the relationship between the basic variables of the subject were confirmed, and the study concluded that there is a strong correlation between the type of leadership style used and organizational effectiveness in achieving the goals of the institution.